Bioanalytical method development and validation of vildagliptin a novel dipeptidyl peptidase IV inhibitor by RP-HPLC method - Pharne, A. B.; Santhakumari, B.; Ghemud, A. S.; Jain, H. K.; Kulkarni, Mahesh J. (International Journal of Pharmacy and Pharmaceutical Sciences, 2012)
A simple, selective, rapid, precise and economical Reverse-Phase HPLC method has been developed and validated for quantitative determination of vildagliptin in plasma. Vildagliptin is a potent dipeptidyl peptidase IV inhibitor used for treatment of diabetes. Tolbutamide is used as an internal standard. The method was carried out with UV Spectrophotometric detection using a Perkin Elmer Series 200 HPLC system equipped with XBridge Shield C18 column (3.5 μm, 4.6x150mm) and a guard column of the same type, at a flow rate of 1.0mL/min. Detection was carried out at 210 nm. The mobile phase consisted of 50mM ammonium bicarbonate (pH 7.8) (solvent A) and acetonitrile (solvent B). The retention times of vildagliptin and tolbutamide were 11.2 min and 13.4 min respectively. The method was developed and tested for linearity range of 10μg/ml to 120μg/ml. The developed method was validated in terms of selectivity, accuracy, precision, linearity, and stability study. The proposed method uses less biological material and the method is MS compatible also. Method can be applicable for pharmacokinetic studies using HPLC or LC-MS.